Structural and functional properties of fava bean albumin, globulin and glutelin protein fractions - Timilehin David Oluwajuyitan; Rotimi Emmanuel Aluko (Food Chemistry: X)
This study reports a comparative evaluation of the physicochemical and functional properties of fava bean albumin, globulin and glutelin proteins. The fava bean globulins had significantly (p < 0.05) higher protein content (88.49 %) than the albumin (83.47 %) and glutelin (86.71 %). Far-UV circular dichroism results indicate low contents of α-helix, but high levels of unordered and β-sheet structures in the albumin and globulin. Higher surface hydrophobicity of the globulins was directly related to formation of oil-in-water emulsions with smaller oil droplet sizes, and better foaming capacity than the albumin and glutelin. The albumin had a broad range (32–92 %) of protein solubility that covers acidic and alkaline pH while glutelin exhibited significantly higher in vitro protein digestibility (77.33 %) when compared to the 75.34 and 71.73 % for globulin and albumin, respectively. We conclude that each fava bean protein fraction may find specific uses as ingredients for the formulation of various food products.